Pengaruh Happiness Terhadap Quality Of Life Pada Pasien Kanker - Suciati Eka Putri; Dyta Setiawati H (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Cancer is one of the biggest health problems in Indonesia and cancer is a group of non-communicable diseases. Cancer makes patients experience changes in physical and psychological conditions that affect the quality of life. The purpose of this study was to determine the effect of happiness on quality of life in cancer patients. This research method uses quantitative methods with a correlational approach. Sampling in this study used a non-probability sampling technique with purposive sampling method. The subjects of this study were cancer patients who underwent chemotherapy at the CISC Foundation in South Kalimantan with a total of 142 subjects. The scale used in this study is the scale of happiness and the scale of quality of life, with the model being the Likert scale. The results of this study are that there is a positive and significant effect between happiness and quality of life in cancer patients undergoing chemotherapy with a coefficient (r) of 0.536 with a value (Sig.) of 0.000.